2002
DOI: 10.1097/00008390-200204000-00005
|View full text |Cite
|
Sign up to set email alerts
|

CD80-mediated induction of immunostimulation in two ocular melanoma cell lines is augmented by interferon-γ

Abstract: Although the transfection of the T-cell costimulatory molecule CD80 cDNA into human tumours can augment their immunogenicity in vitro, its expression alone is ineffective in many tumour systems. We evaluated the influence of CD80 expression on the immunostimulatory activity of ocular melanoma cell lines and determined whether IFN-gamma could enhance the effect. Two ocular melanoma cell lines were transfected with CD80 cDNA. The immunostimulatory capacity of the CD80+ transfectants was determined by their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several reports have indicated that CD80 geneinfected tumor cells can stimulate PBMC activity as effector cells [29,30]. CD80 delivers an important costimulatory signal via binding to its receptor, CD28 and CTLA-4 [29,31,32]. Cancer cells can escape from preexisting CTLs either by a loss of tumor antigen or by down-regulation of costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that CD80 geneinfected tumor cells can stimulate PBMC activity as effector cells [29,30]. CD80 delivers an important costimulatory signal via binding to its receptor, CD28 and CTLA-4 [29,31,32]. Cancer cells can escape from preexisting CTLs either by a loss of tumor antigen or by down-regulation of costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%